Fifth Five Year Plan Approach Paper Union Territory of Pondicherry - Planning Commission (Planning Commission, 1972)
The National Development Council in its meeting held on 30th and 31st May, 1972, considered at length the paper prepared by the Planning Commission on the approach to the Fifth Plan and endorsed the proposals made by the Commission without any change. This approach makes a radical departure from what has hitherto been followed in the first Four plans. the Planning Commission's thesis was that, inspite of the around increase in the per capita income and gross national product in the last two decades of planned development, there are still 200 million people in the country living below the poverty line.
Finance Department Govt. of Pondicherry